요양병원 간호사의 치매 행동심리증상 부담감, 치매태도 및 감정노동이 돌봄행위에 미치는 영향 - 어혜경(Eo, Hye Kyung); 김선호(Kim, Seonho) (근관절건강학회지, 2021)
Purpose: This study was a descriptive research to identify the relationships among burden from behavioral psychological symptoms of dementia, dementia attitude, emotional labor and nurse's caring behavior as well as to clarify factors that affect caring behavior of nurses in long-term care hospital. Methods: For the research, this study collected data from July 8 to July 20, in 2019 with 214 nurses who worked at 10 long-term care hospitals in Chungbuk. The data were analyzed using descriptive statistics, t-tests, Mann-Whitney U test, ANOVA, Pearson's correlation coefficient, stepwise multiple regression with the SPSS 23.0 program. Results: Factors influencing caring behavior of nurses in long-term care hospital were dementia attitudes (β=.549, p<.001), burden from behavioral psychological symptoms of dementia (β=.242, p<.001) and marital status (β=.134, p=.017). These factors explained 33.9% of caring behavior (F=37.35, p<.001). Conclusion: Dementia attitudes were confirmed to be the main variable influencing nurse's caring behavior. Therefore, to improve the caring behavior of dementia patient, it is considered that the development of programs to improve dementia attitudes and in-depth understanding regarding the behavioral and psychological symptoms of dementia is necessary.